METODE MIKROKOLONI (SLIDE CULTURE) SEBAGAI METODE DIAGNOSTIC ALTERNATIVE YANG LEBIH CEPAT UNTUK DIAGNOSIS TUBERCULOSIS PARU - Budi Koendhori, Eko; Harsono, Setio (Lembaga Penelitian Universitas YARSI, 2007)
Despite wide distribution of pulmonary tuberculosis in Indonesia, its diagnosis is still an important issue to be dealt with. Fourty seven sputums from pulmonary tuberculosis patients in Surabaya were examined to detect Mycobacterium tuberculosis using three methods, i.e. the acidfast stain Ziehl Neelsen, microcolony (slide culture) and Lowenstein Jensen. Sputums were collected spontaneously from the patients. All of them were decontaminated and centrifuged. After the supernatant fluids were carefully decanted, the sediments were resuspended in 1 ml of 10 mMphosphate buffer (pH 7.4) and the suspensions were then inoculated on to two 76 x 13 mm glass microscope slides. One of them was stained by Ziehl Neelsen method and the other was inoculated into microcolony media for seven days and the waste suspension was inoculated into LowensteinJensen media. The results of the microcolony method analysis were compared with the Ziehl Neelsen staining. Employing McNemar test, a significant difference was observed between the microcolony method and the Ziehl Neelsen staining (?² = 5,88). The sensitivity and spesificity ofmicrocolony were 100% and 89% while the Ziehl Neelsen were 60% and 84% respectively. In conclusions microcolony method was better compared with the Ziehl Neelsen staining in the detection of Mycobacterium tuberculosis. Microcolony method was able to reduce time required todetect Mycobacterium tuberculosis in patient suspected with pulmonary tuberculosis.